1983
DOI: 10.1111/j.1365-2125.1983.tb02240.x
|View full text |Cite
|
Sign up to set email alerts
|

Assay‐dependent kinetics of heparin: evidence for rapid in vivo activation of heparin.

Abstract: 1 Multiple blood samples were collected over the first 15 min after an i.v. injection of 25 units/kg of heparin in four healthy subjects. Plasma heparin activity in each sample was determined by a chemical neutralization assay using polybrene and a bioassay based on activated partial thromboplastin time. 2 Chemically assayed heparin declined much more rapidly than bioassayed heparin over the first 5-7 min after the dose. Subsequently, both heparin activity vs time curves declined with a similar terminal half-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This is important because although antithrombin activity and anti-factor Xa HA correlated 1:1 using in vitro UH-spiked normal plasmas, using ex vivo samples obtained from patients who were being treated with UH, antithrombin activity of 0.2 to 0.4 U / m L was found to correspond to an anti-factor Xa HA range of about 0.3 to 0.7 U/mL. 3 6 Various investigators 12,13,37 concluded that the difference between in vitro and ex vivo results was probably due to faster in vivo clearance of high-molecular-weight species of heparin, in which antithrombin activity predominates. These findings gave rise to the consensus recommendation that standardization of APTT assays for monitoring UH therapy should be based on ex vivo plasma samples obtained from patients receiving UH therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because although antithrombin activity and anti-factor Xa HA correlated 1:1 using in vitro UH-spiked normal plasmas, using ex vivo samples obtained from patients who were being treated with UH, antithrombin activity of 0.2 to 0.4 U / m L was found to correspond to an anti-factor Xa HA range of about 0.3 to 0.7 U/mL. 3 6 Various investigators 12,13,37 concluded that the difference between in vitro and ex vivo results was probably due to faster in vivo clearance of high-molecular-weight species of heparin, in which antithrombin activity predominates. These findings gave rise to the consensus recommendation that standardization of APTT assays for monitoring UH therapy should be based on ex vivo plasma samples obtained from patients receiving UH therapy.…”
Section: Discussionmentioning
confidence: 99%
“…), and both of these values are lower than the true clearance of heparin (1.29 ml/kg/min), as determined by chemical titration [8], Moreover, the initial distribution phase -this is evident when the plasma curve of chemically titrated heparin is determined after intravenous administra tion of heparin -is not present when the ac tivated partial thromboplastin time is mon itored [9]. Independently from the method used, the half-life of heparin may be modi fied by the coexistence of pathophysiologic states, and it has been demonstrated [10] that it is significantly shorter in patients with pulmonary thromboembolism, but not in those with peripheral thrombophlebitis.…”
mentioning
confidence: 99%
“…The presence of this active process of heparin biodegradation might account for the systematic differenes that may be demonstrated when compar ing the antithrombotic activities of equal amounts of heparin in vitro and in vivo [9]; the higher in vivo activity of heparin in fact might be explained by the transformation to which Heparin is subjected. The higher bio availability of LMWHs after subcutaneous adminstration with respect to intravenous administration might also be explained by a similar process [16], All experimental evidences suggest that no simple model may be used to describe the pharmacokinetics of heparin and LMWHs; only a complex model including a central pooling compartment where the heparin is stored and transformed might explain the various peculiarities of heparin kinetics [23] that are still uncompletely understood be cause of serious methodological shortcom ings, such as those resulting from the fre quent use of indirect measures of heparin concentrations.…”
mentioning
confidence: 99%